Performance of cold-preserved rat liver Microorgans as the biological component of a simplified prototype model of bioartificial liver - Pizarro, María Dolores (2016)
AIM: To develop a simplified bioartificial liver (BAL) device prototype, suitable to use freshly and preserved liver Microorgans (LMOs) as biological component. METHODS: The system consists of 140 capillary fibers through which goat blood is pumped. The evolution of hematocrit, plasma and extra-fiber fluid osmolality was evaluated without any biological component, to characterize the prototype. LMOs were cut and cold stored 48 h in BG35 and ViaSpan® solutions. Fresh LMOs were used as controls. After preservation, LMOs were loaded into the BAL and an ammonia overload was added. To assess LMOs viability and functionality, samples were taken to determine lactate dehydrogenase (LDH) release and ammonia detoxification capacity. RESULTS: The concentrations of ammonia and glucose, and the fluids osmolalities were matched after the first hour of perfusion, showing a proper exchange between blood and the biological compartment in the minibioreactor. After 120 min of perfusion, LMOs cold preserved in BG35 and ViaSpan® were able to detoxify 52.9% ± 6.5% and 53.6% ± 6.0%, respectively, of the initial ammonia overload. No significant differences were found with Controls (49.3% ± 8.8%, P < 0.05). LDH release was 6.0% ± 2.3% for control LMOs, and 6.2% ± 1.7% and 14.3% ± 1.1% for BG35 and ViaSpan® cold preserved LMOs, respectively (n = 6, P < 0.05). CONCLUSION: This prototype relied on a simple design and excellent performance. It’s a practical tool to evaluate the detoxification ability of LMOs subjected to different preservation protocols.